The Application of Cleaner Production in The Small Industry of Amplang Sembelan Crackers in Kuala Village, Selakau Sub-District, Sambas District - Atasasih, Astin; Furwaningsih, Sri Vera; Mentari; Nurizwan; Alamsyah, Riky; Aqilah, Nuriqlima (Journal of Fisheries and Marine Applied Science, 2024)
Clean production in industry is implemented to increase efficiency and profits, while preserving the environment. In the marine and fisheries sector, solid waste is often produced such as bones, shells, skin and fish heads. One example of a fishery product processing business is the production of amplang crackers, which not only have economic value, but also produce waste. Research on the amplang home industry in Kuala Village, Selakau District, Sambas Regency was carried out through field surveys and direct interviews with industry players. In the process of making amplang cracker, the initial stage begins with preparing the raw materials, weeding the mackerel fish, kneading, frying the amplang cracker. The resulting fish skin waste is reprocessed by drying it in the sun like salted fish, while the unprocessed waste is disposed of in landfills or usually directly through pipe disposal. The process of processing Amplang crackers generally does not produce a lot of waste. However, efficiency and cleanliness in the manufacturing process can still be improved. One effort that can be made is to create an SOP (Standard Operating Procedure) for processing amplang crackers and arrange the layout of the equipment used.